Hur ser en användarvänlig ordbok ut? - Rider, Inger Hesslin (Nordiske Studier i Leksikografi, 1995)
User-friendly is a modem catchword, often used about appliances or systems. More and more frequently, it is also used about another type of advanced tool: the dictionary. When choosing a dictionary in earlier days, the most important crite1ion was size. It was assumed that as long as a dictionary contained vast amounts of information it was a good dictionary. It was up to the users to make friends with the dictionary - if they couldn’t or wouldn’t it was their problem and their fault. Present-day publishers realize that it’s their job to get the information across. This paper discusses userfriendliness under headings such as size, scope, contents, editing, typography, user instructions and front and end matter.